Blended online learning: Students' perception and its effect on learning outcomes abstract algebra - Yumiati, Yumiati; Putra, Harry Dwi; Haji, Saleh (IKIP Siliwangi and I-MES, 2025)
In the current digital era, the implementation of blended online learning faces challenges in understanding students' perceptions and its impact on learning outcomes, particularly in Abstract Algebra. This issue is crucial to investigate, as the shift in teaching methods can influence the comprehension of complex algebraic concepts. This research aims to investigate students' perceptions and learning outcomes in abstract algebra courses of blended and asynchronous online learning. The research method used was quasi-experiment. The subject of 27 students is available without being randomly selected. Research instruments using questionnaires and tests. The test consists of eight essay questions. The questionnaire includes 27 closed-ended questions and six open-ended questions. The results showed that students perceived Abstract Algebra subjects as difficult or very difficult. Most students needed help to study the module due to material difficulty thoroughly. In addition, asynchronous online learning is ineffective compared to blended online learning. All students wanted the tutorial asynchronous and synchronous combined (blended online learning). Most students carry out online learning at home using a smartphone device. Students who use blended online learning obtain significantly higher learning outcomes than students who only take it asynchronously.